Organizational Climate Study for the Collaborators of the "Biblioteca Joaquín García Monge of the Universidad Nacional, Costa Rica” - Soto Vargas, Mildred (2017)
Every organization, institution or company seeks excellence, efficiency and effectiveness to achieve, in the best way, the goals and objectives proposed in the established times. The role played by the human resource is essential to perform the tasks optimally, which contributes to the development of the processes, to fulfill its mission and vision. Recognize that the human resource is motivated and committed; that the company or institution provides an appropriate infrastructure; and that, in addition, taking the collaborator into account as a fundamental part of the institution, will allow the creation of an adequate organizational climate.This research work is based on the application of an organizational climate consultancy for the collaborators of the Joaquín García Monge Library of the National University of Costa Rica, done by the collection of information through the application of a data collection instrument (questionnaire). Based on the result of the application of the instrument, the variables that allow measuring the working environment conditions will be known. With the analysis of the corresponding results, it will be possible to detect the different factors that affect the organizational climate of the workplace, which will be the main input to make an improvement proposal, in order to obtain a better work environment.At the operational level, the proposal focuses on conducting a participatory workshop at the headquarter level, where the thematic axes will be communication and teamwork, evaluated by means of individual and group dynamics. Being focused on the headquarters of the work center, it is expected that it be replicated in the different sections.